Decolonizing Knowledge and Academic Practices through collaborative methodology: Reflections on Collaborative filmmaking with Indigenous Students in the Peruvian Amazon - Jorge Ruiz Zevallos (New Area Studies)
This article reflects on a recent collaborative filmmaking experience in the Peruvian Amazon with indigenous students at the intercultural University of Nopoki. It draws on the theoretical notions of decoloniality of knowledge and knowledge production (Mignolo & Walsh, 2018), functional and critical interculturality (Tubino & Flores, 2020), participatory visual methodologies (Mitchell, De Lange, & Moletsane, 2017), and the crucial input of indigenous knowledge (Rose, 2018). It focuses on the moments of intersection where collaboration provided new insights into the design and methodology of the research, the use of technology, and the distance between the theoretical framework and the experiential (vivencial) knowledge of the participants. Thus, underscoring that research and knowledge production should incorporate local knowledge from the Global South to continue its adaptable line (Finck Carrales, 2021).